Navigating Employment Pathways and Supports Following Brain Injury in Australia: Client Perspectives. Issue 2 (13th December 2016) - McRae, Philippa; Hallab, Lisa; Simpson, Grahame
Abstract : This study investigated the vocational rehabilitation experiences of 29 clients, up to 14 years post brain injury. Data obtained from participant interviews were thematically analysed by employment pathway ('return to pre-injury employment', 'job seeking' and 'not worked since injury'). A total of nine themes were identified. Across all pathways, participants identified the importance of working, impact of injury and their own determination. The content for the remaining themes (understanding, adjustment, access, support, disclosure of injury, intervention) varied by pathway, reflecting the differing perspectives arising from integrating back into a familiar workplace versus seeking new employment. In conclusion, programme approaches to vocational rehabilitation need to be tailored to the individual circumstances, opportunities and support needs of people with brain injury pursuing these different pathways.